Tourism And The Emergence Of Nation-States In The Arab Eastern Mediterranean, 1920s-1930s - Daam, Jasmin (Critical, Connected Histories, 2023)
In the aftermath of World War I, the beaten paths of tourism guided an increasing number of international tourists to the hinterlands of the Arab Eastern Mediterranean, where they would admire pyramids and Roman ruins. Yet they were not the only visitors: Arab nationalists gathered in summer resorts, and Yishuvi skiing clubs practised on Lebanese mountain slopes. By catering to these travellers, local tour guides and advocates of tourism development pursued their agendas. The book unearths unexpected connections between tourism and the emergence of nation-states in Egypt, Palestine, Syria and Lebanon. Arab middle-class actors striving for independence, Zionist settlers and mandate officials presented their visions of the post-Ottoman spatial order to an international audience of tourists. At the same time, mobilities and infrastructures of tourism shaped the material conditions of this order. Tourism thus helps us to understand the transformations of Arab societies in their global context, and its history is a colourful story of the emergence of the modern Middle East.